Enhancing Capacity for Knowledge Transfer - Gorjestani, Nicholas (World Bank, Washington, DC, 2012)
This article proposes a framework for reflection and action by Bank staff to better broker and adapt knowledge to help countries and communities enhance their capacity to deliver results. The focus is on identifying potential actions that would help nurture critical staff behavioral competencies that underpin effective knowledge transfer.